Presence of Trihalomethanes in ready-to-eat vegetables disinfected with chlorine. Issue 12 (2nd December 2017) - Coroneo, Valentina; Carraro, Valentina; Marras, Barbara; Marrucci, Alessandro; Succa, Sara; Meloni, Barbara; Pinna, Antonella; Angioni, Alberto; Sanna, Adriana; Schintu, Marco
ABSTRACT: Trihalomethanes (THMs) – CHCl3, CHCl2 Br, CHClBr2 and CHBr3 – are drinking water disinfection by-products (DBPs). These compounds can also be absorbed by different types of foods, including ready-to-eat (RTE) fresh vegetables. The potential absorption of THMs during washing of RTE vegetables could pose a potential risk to consumers' health. The concentration of THMs in the water used in the manufacturing process of these products shall not exceed the limit of 100 or 80 µgL −1 according to European Union (EU) and United States legislation, respectively. By contrast, there is little information about the presence of such compounds in the final product. This study evaluated the concentration of THMs in different types of RTE vegetables (carrots, iceberg lettuce, lettuce, mixed salad, parsley, parsley and garlic, rocket salad, valerian) after washing with chlorinated water. In the 115 samples analysed, the average value of total THMs was equal to 76.7 ng g −1 . Chloroform was the THM present in the largest percentage in all the RTE vegetables. These results show that the process of washing RTE vegetables should be optimised in order to reduce the risk for consumers associated with the presence of DBPs.